Ritual Performances in the Nāṭyaśāstra II. Food Offerings - Thomas Kintaert (Ksiegarnia Akademicka Publishing, 2018)
In the pursuit of a better understanding of how theatrical performances relate to ritual ones in Bharata’s Nāṭyaśāstra, the whole work has been scrutinized for relevant data. This data can be assigned to three major categories: (1) prescriptive information on rituals to be performed prior to a theatrical spectacle; (2) prescriptions regarding the theatrical representation of rituals within a play; and (3) miscellaneous references that, often incidentally, afford additional insights into individual aspects of ritual performances. In view of the large extent of the compiled information, the latter is at first systematically presented in separate articles covering individual aspects of ritual performances, before being considered as a whole in the theoretical reflections and conclusions of the final article. Whereas the first article of the series dealt with a wide range of ritual items, the present one specifically looks at ritual food offerings.